Un intelectual en el exilio: Mondolfo en la Universidad Nacional de Tucumán (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
Rodolfo Mondolfo, a renowned professor at the University of Bologna, was one of the signatories of the Anti-Fascist Manifesto. Racial laws excluded him from his position in 1938, leading to his decision to go into exile in Argentina. This article highlights two aspects of the period following that date: first, his exile, facilitated by the efforts of the Italian community and his integration into Argentine universities; second, the particular conditions of his presence at the Faculty of Philosophy and Letters of the National University of Tucumán. We highlight two conditions of his teaching in Tucumán: 1. Mondolfo had already been reinstated in his position at the University of Bologna, but he had decided not to return to live in Italy. 2. The Faculty of Philosophy and Letters at the UNT has not yet celebrated its tenth anniversary since its institutionalization, while the Italian scholar is already 71 years old. These conditions make his outlook on the university and university policy, his considerations on the history of philosophy and action, as well as the rigor of his teaching and intellectual output—notwithstanding his exile—founding features of the nascent faculty.
Keywords: exile; university; praxis; Faculty of Philosophy and Letters of the UNT; philosophy